Initial Impressions Determine Behaviours: Morality Predicts the Willingness to Help Newcomers - Pagliaro, Stefano; Brambilla, Marco; Sacchi, Simona; D’Angelo, Manuela; Ellemers, Naomi (2013)
Prior research has demonstrated the impact of morality (vs. competence) information for impression formation. This study examines behavioral implications of people’s initial impressions based on information about their morality vs. competence in a workplace. School teachers and employees (N = 79) were asked to form an impression of a new school manager (i.e. a prospective boss), who was presented as High vs. Low in Morality and High vs. Low in Competence. Results showed that morality information rather than competence information determined initial emotional responses to the new manager, which mediated willingness to help the newcomer adjust in task and social contexts. Results are discussed in terms of their theoretical and practical implications and future research directions are outlined.
Keywords: Behaviour; Morality; Impression formation